Acute sleep deprivation in healthy adults is associated with a reduction in left atrial early diastolic strain rate - SARI, İBRAHİM (SPRINGER HEIDELBERG, 2013)
Sleep deprivation (SD) is known to be associated with adverse cardiovascular events. Strain and strain rate measure the local deformation of the myocardium and have been used to evaluate atrial phasic function in various disease states. The aim of the study was to investigate whether strain rate imaging enables the identification of left atrial dysfunction in otherwise healthy young adults with acute SD which has not been studied previously. Adequate echocardiographic images of 27 healthy volunteers were obtained both after a night with regular sleep and after a night with SD. Tissue Doppler-derived strain and strain rate were measured from the apical four- and two-chamber views of the left atrium, and global values were calculated as the mean of all segments. Measurements included peak systolic strain, systolic strain rate (S-Sr), early diastolic (E-Sr) and late diastolic (A-Sr) strain rate. Phasic left atrial (LA) volumes and fractions were also calculated. There was no significant difference in the traditional parameters of atrial function and LA volumes. Subjects had similar S-Sr, A-Sr and global atrial strain values after the night of sleep debt when compared after regular sleep, whereas they had significantly reduced E-Sr values (mean (SD) 3.2 (0.7) s(-1) vs 3.7 (0.6) s(-1), p < 0.001). Moreover, global E-Sr showed a significant correlation with sleep time (r = 0.554, p < 0.001). Acute SD in healthy adults is associated with a reduction in LA early diastolic strain rate in the absence of geometric alterations or functional impairment of the left atrium, raising the possibility that chronic SD may more profoundly affect LA function and thereby promote the occurrence of atrial fibrillation.
Keywords: Sleep deprivation; Tissue Doppler imaging; Strain; Strain rate; Left atrial function; RISK-FACTOR; DURATION; APNEA; ECHOCARDIOGRAPHY; CARDIOVERSION; HYPERTENSION; DISPERSION; VELOCITY; SYSTEM; VOLUME